Expression of fatty acid related gene promotes astaxanthin heterologous production in Chlamydomonas reinhardtii - Sun, Jin-peng; Wei, Xue-hong; Cong, Xiao-mei; Zhang, Wen-hua; Qiu, Le-Xin; Zang, Xiao-nan (Frontiers in Nutrition, 2023)
Natural astaxanthin is a high-value ketone carotenoid mainly derived from Haematococcus pluvialis, which is an excellent antioxidant for human consumption. To study the role of lipids in accumulation of astaxanthin, the H. pluvialis-derived astaxanthin synthesis pathway genes (β-carotene ketolase gene, BKT and β-carotene hydroxylase gene, BCH) and fatty acid elongation gene (mitochondrial trans-2-enoyl-coa reductase gene, MECR) were heterologously co-expressed in C. reinhardtii. Zeaxanthin, the precursor of astaxanthin synthesis, was significantly increased after BKT and BCH were expressed. In contrast, the α-carotene that competes with astaxanthin synthesis for lycopene decreased significantly. This redistribution of carbon flow was conducive to the synthesis of astaxanthin. In addition, the transformant only expressed astaxanthin metabolism related genes (BKT, BCH) would lead to an increase in total lipid, a decrease in monounsaturated fatty acids and an increase in polyunsaturated fatty acids. On this basis, the expression of MECR gene further increased the total lipid, and the relative content of different fatty acids also changed. The astaxanthin content of algal strains transformed with BKT and BCH genes was nearly 50% higher than that of the wild type. On this basis, the astaxanthin content of transformants expressing MECR gene related to long-chain fatty acid synthesis was increased by 227.5%. In this study, an astaxanthin production model similar to H. pluvialis by combining carotenoid metabolism and fatty acid metabolism was constructed in C. reinhardtii. The results suggest that the increase in astaxanthin is indeed linked to the regulation of fatty acid metabolism, and this link may involve the type of fatty acids and the dynamics of astaxanthin ester in cells. The strategy of promoting the synthesis of fatty acids has potential to achieve efficient production of astaxanthin in C. reinhardtii.